THE ROLE OF MOTIVATION AS MEDIATION IN IMPROVING EMPLOYEE PERFORMANCE IN THE GOVERNMENT OF SURABAYA CITY, EAST JAVA - Sumiati Sumiati (Jurnal Manajemen dan Kewirausahaan, 2021)
This paper discusses the causal relationship between servant leadership, professionality, work culture, motivation, and the performance of Surabaya City government employees. One model is proposed to examine the role of motivation as a mediating variable in the indirect relationship of servant leadership, professionality, work culture and performance. The population is the government employees of Surabaya City. Analysis by SEM, on 290 respondents, using the convenience sampling method. The results show that the model is accepted, and also show that servant leadership, professional, and work culture has an effect on motivation. Servant leadership, work culture and motivation have an effect on employee performance. Motivation is a positive mediating variable in the relationship between servant leadership, professional, and work culture with performance.